Insecticide susceptibility of Phlebotomus argentipes in visceral leishmaniasis endemic districts in India and Nepal. - Diwakar Singh Dinesh; Murari Lal Das; Albert Picado; Lalita Roy; Suman Rijal; Shri Prakash Singh; Pradeep Das; Marleen Boelaert; Marc Coosemans (PLoS Neglected Tropical Diseases, 2010)
OBJECTIVES: To investigate the DDT and deltamethrin susceptibility of Phlebotomus argentipes, the vector of Leishmania donovani, responsible for visceral leishmaniasis (VL), in two countries (India and Nepal) with different histories of insecticide exposure. METHODS: Standard WHO testing procedures were applied using 4% DDT and 0.05% deltamethrin impregnated papers. The effect of the physiological status (fed and unfed) of females on the outcome of the bioassays was assessed and the optimal time of exposure for deltamethrin was evaluated on a colony population. Field populations from both countries were tested. RESULTS: Fed and unfed females responded in a similar way. For exposure time on field samples 60 min was adopted for both DDT and deltamethrin. In Bihar, knockdown and mortality with DDT was respectively 20 and 43%. In Nepal almost all sand flies were killed, except at the border with Bihar (mortality 62%). With 0.05% deltamethrin, between 96 and 100% of the sand flies were killed in both regions. CONCLUSIONS: Based on literature and present data 4% DDT and 0.05% deltamethrin seem to be acceptable discriminating concentrations to separate resistant from susceptible populations. Resistance to DDT was confirmed in Bihar and in a border village of Nepal, but the sand flies were still susceptible in villages more inside Nepal where only synthetic pyrethroids are used for indoor spraying. The low effectiveness of indoor spraying with DDT in Bihar to control VL can be partially explained by this resistance hence other classes of insecticides should be tested. In both countries P. argentipes sand flies were susceptible to deltamethrin.